22 Inclusion and diversity representation in GOSH apprenticeships. (23rd February 2023) - Manget, Jesse; Fletcher, Hannah; Mahmood, Aliea; Knight, Alice; O'Sullivan-Whiting, Laurence; Khan, Moeen
Abstract : Background: Apprenticeships have been an area of growing strength in education provision at GOSH. With over 200 apprentices across more than 35 different pathways, we have created opportunities for existing staff to develop and progress into rewarding roles. Captured data demonstrates that apprenticeships are inclusive, offering opportunities to applicants from a diverse range of backgrounds and protected characteristics as defined by the Equality Act 2010. Methods: Apprentice equality, diversity and inclusion data was collected over a 5-year period from 2017 to 2022. The data is anonymised and includes information on age, religious beliefs, disability, ethnicity, gender, and sexual orientation. Further data analysis reveals the current (2022) split between clinical and non-clinical apprenticeships, and the split between existing staff and newly recruited staff on apprenticeships. Results: Equality, diversity, and Inclusion (EDI) data demonstrates an increase in apprenticeship inclusion, particularly data concerning sex, disability, age, religious beliefs, and race. Further data shows development of existing staff and high-level apprenticeships that positively impacts retention. Providing a diverse staff pool for patient care through a workforce that reflects the local population. Discussion: The data shows that although apprenticeships have always demonstrated inclusion, we now see this extended towards EDI data. For example, (i) we have seen increase in male inclusion, this is difficult to explain without further investigation, (ii) In relation to age, a change in associated stigmas with apprenticeships (e.g., they are for school leavers) and availability of higher-level programs has seen exponential growth in uptake and recruitment to apprenticeships in the over 24 years age group in the last two years. Improved data collection in recent years may explain some of the results, however a larger pool could improve validity of results. Conclusion: It could be concluded that an increase in apprenticeship numbers will directly improve the EDI data for the trust.